A Hopeless Determination of the Day of Judgment Based on Being Hope (Raja') Equivalent to Ratification in the Verse 7 of Surah Junus - Sayyedeh Fatemeh Kiaei; Sayyed Ghasem Kiaei (آموزه‌های قرآنی)
The Quran exegetes have determined the term “raja'-hope” in the statement ﴿لَا یَرْجُونَ لِقَاءَنَا﴾ (Those who rest not their hope on their meeting with Us) with different possibilities such as: fear, desire, expectation and ratification. Among this while ratification (تصدیق) is of the meanings for being far away from the meaning which has been created the word “hope” (raja') it is necessary to determine a relationship mechanism between it and “hope” (raja'). The exegetes have not examined it and this problem faces serious ambiguity and challenges. The other problem which includes most of the aforementioned exegetic dialectics such as ratification -confirmation-(تصدیق) is the absence of attention to the motivational approach of the verse in the propagation of the hope -centered hereafter instead of argumentation- centered hereafter. A point Which is in spite of having proofs such as the selection and order of the verse vocabulary in the exegeses has been neglected and has not paid attention. Meaning with studying the exegeses, the mind of the addressee concentrates on belief in al-ma'ad (day of resurrection) and its unpleasant outcomes of turning aside from belief in al-ma'ad (the day of resurrection) as a religious principle while the verse is going to open another window except what indicates the day of resurrection as a belief and compulsory religious principle for the addressee and to motivate his mind powers in relation to the capacity of the hope of al-ma'ad (the day of resurrection) and briefly and totally to promote a tendency to the resurrection and not the resurrection belief. With aim to review and analyze the opinion which views “hope” (raja') being equivalent to confirmation (تصدیق) and presenting this claim that the verse specifically with the vital subject of al-ma'ad (the day of resurrection) is going to create a tendency (ambition) not belief to the day after this note has been adopted.